The in vitro efficacy of biofilm removal from titanium surfaces using Er:YAG laser: Comparison of treatment protocols and ablation parameters. Issue 1 (29th June 2021) - Polak, David; Shani‐Kdoshim, Sharon; Alias, Mary; Shapira, Lior; Stabholz, Ayala
Abstract: Background: The aims of the present study were to compare the antibacterial effect of Er:YAG laser with other acceptable decontamination methods and to single out the optimal laser device parameters for effective bacterial elimination. Methods: A multispecies biofilm which was composed of Streptococcus sanguis, Actinomyces naeslundii, Porphyromonas gingivalis, and Fusobacterium nucleatum was grown on sandblasted and acid‐etched (SLA, homogeneous moderately microrough, and nanosmooth surface) titanium disks. The biofilm was removed from the coated disks by hand curets, ultrasonic device, nylon brush (dental polishing prophy cup), or Er:YAG. Additionally, different parameter combinations of the laser machine were examined to reach an optimal lasing power for bacterial elimination/reduction. Residual biofilm samples were stained with bacterial live/dead staining and quantified using a fluorescent microscope. Results: A multispecies biofilm was accumulated on the SLA titanium surfaces exhibiting cluster distribution next to bacteria‐poor areas. Hand curets, nylon brushes, and the ultrasonic device showed limited capability to effectively remove the biofilm from the SLA surfaces as opposed to the Er:YAG which displayed a superior ability to remove the biofilm. All Er:YAG parameter combinations that were evaluated as well as the tested "tip to target" distances showed similar excellent anti‐biofilm effects. Furthermore, we observed that the Er:YAG capability of biofilm removal is not only due to its light emission, but depends on its water irrigation as well. Conclusions: Er:YAG laser has an excellent biofilm removal capability compared with hand curets, ultrasonic devices, or nylon brushes even when low energy parameters and low power settings are used. Additionally, an excellent antibacterial effect can be reached using a non‐contact mode of 1 to 5 mm "tip to target" distance.